Pembelajaran Interaktif dengan Mentimeter pada Mahasiswa Keperawatan: Kajian Kemanfaatan dan Determinan Sosial Ekosistem Lahan Basah - Annisa Febriana; Rahmi, Yuza Olsi; Lestari, Hayatus Sa'adah Ayu; Muthmainnah, Muthmainnah; Heryyanoor, Heryyanoor (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Interactive technology-based learning is an innovative strategy to enhance nursing students' understanding, particularly on multidisciplinary topics such as wetland ecosystems. This study aims to evaluate the effectiveness of using Mentimeter as an interactive learning tool in improving nursing students' knowledge of the benefits and social determinants of wetland ecosystems. The research method used a quasi-experimental design with pretest and posttest design without a control group. The participants were 72 seventh-semester nursing students enrolled in the Wetland Ecosystem course. The intervention was conducted through offline learning sessions that utilized Mentimeter for quizzes, polls, and discussions focused on the benefits and social determinants of wetlands. The results showed an increase in students knowledge following the intervention. The pretest results indicated that 65% of students were in the “good” knowledge category, which increased to 87% in the posttest. The “sufficient” category decreased from 25% to 10%, and the “poor” category dropped from 10% to 4%. Overall, there was a 22% improvement in knowledge, with the majority of students reaching the “good” category. Student responses to the use of Mentimeter reflected a high level of satisfaction. Most students reported that this method enhanced their active participation, increased learning motivation, and made it easier to understand the material through engaging approaches. In conclusion, interactive learning using Mentimeter has proven effective in increasing nursing students' knowledge of the benefits and social determinants related to wetland ecosystems.